Optimization of Enzymatic Bioremediation of Oil Contaminated Soil by Laccase from Marasmiellus palmovorus using Response Surface Methodology - Agus Jatnika Effendi; Sri Harjati Suhardi; Yollanda Chekti Kirana Arun Surya Widi; Khomaini Hasan; Dion Awfa; Rendana Saputra (Universitas Diponegoro, 2021)
Crude oil contamination is considered highly toxic and poses a significant environmental problem. As an alternative, the laccase enzyme showed high performance for removing various toxic contaminants, particularly oil-contaminated soil (i.e., total petroleum hydrocarbon). However, previous studies mainly tested the performance of laccase under irrelevant environmental conditions (i.e., artificially contaminated soil) with a limited number of soil samples, which can lead to bias optimization results for assessing laccase performance. Two types of natural oil-contaminated soils were tested under various reaction times and various concentrations of laccase extracted from Marasmiellus palmovorus. In addition, response surface methodology was used to find the maximum degradation of total petroleum hydrocarbon (TPH). The maximum degradation of TPH from soil A and soil B were 48.57% and 54.1%, respectively. Moreover, the performance of the laccase enzyme for oil recovery was also tested, with the percentage of oil recovery being 9.89% and 10.1 % for soil A and soil B, respectively. SARA fraction analysis indicated that laccase enzyme preferentially degraded highly polar SARA fraction (i.e., asphaltene and resin). In general, the application of laccase for the enzymatic remediation of oil-contaminated soils was practical. Hence, the use of laccase for environmental application is still promising.